Pengaruh pemberian ekstrak daun alfalfa (Medicago sativa) terhadap kadar glukosa darah tikus hiperkolesterolemia - Joyeti Darni, S.Gz., M.Gizi (University of Darussalam Gontor, 2018)
Background: Hypercholesterolemic as an indicator of cardiovascular disease is a major cause of morbidity and mortality in the world. Increased oxidative stress in hypercholesterolemic triggers lipid peroxidation effect directly on the cell membrane damage and initiate various diseases. The use of natural materials with relatively few side effects is an hyperglycemic management alternative. Alfalfa stimulation of insulin secretion, and also improves insulin function by reducing plasma glucose. Experimental studies showed that Alfalfa leaf extract had an effective hypoglycemic activity. Objectives: To determine the effect of Alfalfa leaf extract on blood glucose level of hypercholesterolemic rats. Method: Pre-posttest randomized control group used twenty eight male Sprague Dawley rats were randomly divided into four groups, Sprague Dawley rats without treatment (control), Sprague Dawley rats with extract at dose 20 mg/200 g/d (X1), dose 40 mg/200 g/d (X2), dose 60 mg/200g/d (X3) for 21 days after the rats got hypercholesterolemic. Blood glucose level was measured by GOD-PAP method. Hypothesis test was analyzed by One Way Anova continued by Post hoc LSD test. Results: Alfalfa extract signiﬁcant decrease in serum total cholesterol (p<0.000). Conclusion: The treatment of Alfalfa (Medicago sativa) leaf extract gives an effect of lower blood glucose level.